The Profile of Free Teamwork Software - Wojtowicz, Radosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The article is the short introduction to the questions relating to the teamwork and software which supports collaborative work. We can notice a growing interest of free operating systems and the article focuses on entirely free systems therefore. The several most important definitions are introduced in the first part of the article. The most important is showed in the second part of the study: the profile of three chosen groupware systems which seem to be representative for the described class of computer software.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 120-127